Age-Dependent Impairment of Somatosensory Response in the Amyloid Precursor Protein 23 Transgenic Mouse Model of Alzheimer's Disease - Mueggler, Thomas (J Neurosci, 2003)
Quantitative functional magnetic resonance imaging was applied to characterize brain function in amyloid precursor protein 23 (APP23) transgenic mice, which reproduce the neuropathological alterations associated with Alzheimer's disease. Electrical stimulation of the paw led to cerebral blood volume increases in the contralateral somatosensory cortex. In APP23 mice this hemodynamic response decreased with increasing age of the animal and with increasing stimulus amplitude as compared with wild-type animals. The age-dependent dysfunction in APP23 mice may be attributed in part to a compromised cerebrovascular reactivity. Quantitative functional brain mapping that uses standardized sensory inputs should allow for assessment of disease progression and therapy response (e.g., passive immunization against β-amyloid) in patients also.